Prevalence of pain in hospitalized patients in the Neurosurgery Service of a Tertiary University Hospital in Madrid, Spain - Ortega-Zufiría, José M. (2021)
Objectives: to measure the prevalence and intensity of acute pain in hospitalized patients in the Neurosurgery Service of a Tertiary Hospital, using a numerical verbal scale, the Visual Analogue Scale (VAS) for its evaluation. Material and methods: observational, cross-sectional study to evaluate acute pain. All patients admitted to the ward during November 2019 are included and those with limitations to understand or evaluate pain according to VAS are excluded. Results: of the total of 120 patients admitted to the ward during the study period, 40 were excluded because they did not meet the inclusion criteria. Eighty patients with a high prevalence of pain (76.61%) were analyzed, with a mean score of 3.47 ± 0.78. Of those who report pain, 20% is mild, 40% moderate and 40% intense. For pathologies, the highest values ​​correspond to post-intervention. Hospital analgesic protocols were applied in all cases and no patient went to the emergency room due to pain after hospital discharge. The main limitation of the study was that the VAS score was not adequately collected in all patients. Conclusions: the prevalence of pain in a neurosurgery ward is high (76.61%), with average scores (3-4, moderate pain) that require improving our analgesic strategies and its measurement. Malignant diseases, predominantly intracranial, were associated with greater pain.